2012
DOI: 10.1136/injuryprev-2012-040496
|View full text |Cite
|
Sign up to set email alerts
|

Distracted driving: mobile phone use while driving in three Mexican cities

Abstract: Mexico has a significant road traffic injury and mortality burden, and several states/municipalities have begun passing legislation restricting mobile phone use while driving (MPUWD). Little information is available about the prevalence of MPUWD in Mexico. This study measures the prevalence of mobile phone talking and texting among drivers in three cities, and identifies associated demographic and environmental factors. Two rounds of roadside observations from a group of randomly selected automobile drivers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…It also must be acknowledged that the data were collected at a deliberately chosen location, selected because of its typical traffic congestion. Thus the rate of texting at the light seen at this site cannot be generalized, as could be done from a multi-site study [ 19 , 20 ]. Further, the window of observation for moving vehicles was inherently briefer than for stationary ones.…”
Section: Discussionmentioning
confidence: 99%
“…It also must be acknowledged that the data were collected at a deliberately chosen location, selected because of its typical traffic congestion. Thus the rate of texting at the light seen at this site cannot be generalized, as could be done from a multi-site study [ 19 , 20 ]. Further, the window of observation for moving vehicles was inherently briefer than for stationary ones.…”
Section: Discussionmentioning
confidence: 99%
“…National prevalence estimates of CPU of drivers range between 5% and 10%; Pickrell and Ye, 2011 , Townsend, 2006 , Vera-López et al, 2012 however, this may be underestimating the problem as many U.S. drivers self-report CPU while driving ( Braitman and McCartt, 2010 ). Nearly 40% of all drivers report talking and 13% report texting while driving at least once a week ( Braitman and McCartt, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…self-report) as individuals are prone to report lesser use due to social desirability. Evidence from two observational studies reported a higher prevalence of cellphone use in the same context [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%